Immigration policy review and comparison of Germany, Italy and the Netherlands - Vo, Ha An; Klosová, Anna, 1942-; Bolotov, Ilya; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
The thesis reviews and provides comparison of immigration policies of Germany, Italy and the Netherlands from post-WW2 years to the late 1990s. With regards to the different historical, cultural and social background of each country the dissertation thesis defines the unique approach to immigration and perception of immigrants in each country. The ultimate aim of the thesis is to explain the circumstances that lead to the specific events in the history of immigration policies of the countries in question and bring comprehension in this often overlooked matter.
Vedoucí práce: Anna Klosová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: economics of globalisation and european integration [obor dipl. práce]; diplomové práce; master's theses